1987
DOI: 10.1152/ajpheart.1987.252.3.h622
|View full text |Cite
|
Sign up to set email alerts
|

The mitochondrial adenosine 5'-triphosphatase in slow and fast heart rate hearts

Abstract: A survey of 12 species has revealed that reversible ischemia-induced protonic inhibition of the cardiac muscle mitochondrial adenosine 5'-triphosphatase (ATPase) described by this author earlier (Rouslin, W. J. Biol. Chem. 258: 9657-9661, 1983) occurs only in animals with heart rates lower than approximately 200 beats/min. It was thus fully demonstrable in rabbit, dog, sheep, human, pig, and beef heart mitochondria. In contrast, the in situ ATPase inhibition was completely absent in six smaller species capable… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
66
1

Year Published

1991
1991
2015
2015

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(68 citation statements)
references
References 0 publications
1
66
1
Order By: Relevance
“…ATP synthase capacity in control cells incubated in the abovementioned centrifugation buffer without any further additions was 14 m-units/mg of protein (mean, n = 12). This value is of the same order of magnitude as observed in previous studies [21,22]. No significant difference in the ATP synthase capacity could be observed in the two hearts where both atrium and ventricle were examined.…”
Section: Measurement Of Atp Synthase Capacity In Heart Mitochondriasupporting
confidence: 87%
See 1 more Smart Citation
“…ATP synthase capacity in control cells incubated in the abovementioned centrifugation buffer without any further additions was 14 m-units/mg of protein (mean, n = 12). This value is of the same order of magnitude as observed in previous studies [21,22]. No significant difference in the ATP synthase capacity could be observed in the two hearts where both atrium and ventricle were examined.…”
Section: Measurement Of Atp Synthase Capacity In Heart Mitochondriasupporting
confidence: 87%
“…This regulatory protein has been found in human hearts [22]. In isolated mitochondria IF, has been shown to respond to the potential across the mitochondrial inner membrane [25,26], binding to ATP synthase when the potential is low as in uncoupled or anoxic mitochondria.…”
Section: Discussionmentioning
confidence: 99%
“…124 Consistently, both in vitro and in vivo experimental models demonstrated that during ischemia the ATPase activity is (at least partially) inhibited by the reversible binding of IF 1 , thus mitigating ATP depletion. Indeed, in ischemic hearts of dog, 161 goat 162 and rabbit 163 the loss of ATPase activity correlates with an increased IF 1 content. Down-regulation of F-ATP synthase activity is also observed in anoxic cardiomyocytes, although the IF 1 contents were not measured.…”
Section: F-atp Synthase and Ptp Formation In The Heartmentioning
confidence: 98%
“…IF-1 in the heart is expressed differently in several mammalian species, and this has been subdivided into "fast heart rate species" (rat, mice, and birds) that express low levels of IF-1 and "slow heart rate species" (dogs and rabbits) that express high levels of IF-1 [10,[47][48][49]. It is presently unclear how these differences can affect the pathogenesis of ischemia in the different species.…”
Section: If-1 Proteinmentioning
confidence: 99%